Evaluation of the Factors Influencing Residual Oil Evolution after Alkali/Surfactant/Polymer Flooding in Daqing Oilfield - Chunlin Nie; Xiaolin Wu; Zhaowei Hou; Junjian Li; Hanqiao Jiang (Energies, 2022)
The alkali/surfactant/polymer (ASP) flood has long been considered to reduce residual oil saturation significantly after waterflood. This paper provides an experimental investigation of the factors (permeability, pore structure, ASP formula, injection volume, viscosity, and injection volume) that influence the evolution of residual oil after ASP flooding. ASP flood experiments were conducted on the cores drilled in Daqing field, and two-dimensional real-structure micromodels were constructed based on these cores. For the ASP core flood experiments, X-ray computed tomography imaging was used for the visualization of the residual oil evolution. For the ASP micromodel flood experiments, images of the residual oil distribution were obtained using a microscope with a 5× magnification objective. The results showed that as water saturation increased during the flood, the proportion of oil clusters decreased, and the proportion of oil droplets first increased and then decreased. For the cores with smaller pore throats and more complex pore structure, the residual oil became more scattered. In this case, the oil clusters became smaller, and oil droplets became easier to retain. An increased injection rate improved the emulsification, resulting in more residual oil in small pores getting replaced. Increasing the viscosity by increasing the polymer concentration improved the sweep efficiency, mainly because residual oil in large pore throats was displaced, but had a negative impact on emulsification. Increasing the viscosity of the injection fluid was shown to have a negative impact on improving the oil recovery ratio, because the mobilization of residual oil in smaller pores was greatly impacted by emulsification. The effect of increasing injection volume on improving recovery was more pronounced for cores with lower permeability.